Nanoscale detection and real-time monitoring of free radicals in a single living cell under the stimulation of targeting moieties using a nanodiamond quantum sensor - Kaiqi Wu; Qi Lu; Maabur Sow; Priyadharshini Balasubramanian; Fedor Jelezko; Tanja Weil; Yingke Wu (Functional Diamond, 2024)
Intracellular radicals play important roles in cell signaling and regulation of growth factors, cytokines, transcription, apoptosis, and immunomodulation, among others. To gain a more comprehensive understanding of their biological functions from a spatio-temporal perspective, there is a great need for nanoscale sensitive tools that allow real-time detection of these reactive species. Currently, intracellular radical probes are based on chemical reactions that could significantly alter radical levels during detection. Due to the excellent biocompatibility and favorable photophysical properties of nitrogen-vacancy (NV–) centers in fluorescent nanodiamonds (fNDs), the fNDs can serve as a powerful and chemically inert nanotool for intracellular radical detection. In this study, a positively charged nanogel (NG) coating was prepared to prevent the precipitation of fNDs and promote cellular internalization. After internalization of nanodiamond-nanogels (fND-NGs), different stimulators, namely somatostatin (SST), triphenylphosphonium (TPP), and trans-activator of transcription (TAT) peptide, which are widely used cell- or organelle-targeting ligands in medicine, drug delivery, and diagnostics, were applied to stimulate the cells. In parallel, the intracellular radical changes under stimulation of SST, TPP, and TAT ligands were monitored by fND-NGs in a home-built optically detected magnetic resonance (ODMR) microscope. Our method allows for detecting intracellular radicals in-situ and monitoring their real-time changes during incubation with the targeting ligands in a single living cell. We believe that our method will provide insights into the generation of radical stress in cells, which could improve our fundamental understanding of the pharmacology and signaling pathways of widely used cell- and organelle-targeting ligands associated with free radicals.